2007
DOI: 10.1017/s1368980007000109
|View full text |Cite
|
Sign up to set email alerts
|

Personal and lifestyle characteristics predictive of the consumption of fast foods in Australia

Abstract: Objective: To identify key predictors of fast-food consumption from a range of demographic, attitudinal, personality and lifestyle variables. Methods: We analysed data from a nationwide survey (n 5 20 527) conducted in Australia by Nielsen Media Research. Items assessing frequency of fast-food consumption at (1) eat in and (2) take away were regressed onto 12 demographic, seven media consumption, and 23 psychological and lifestyle variables, the latter derived from factor analysis of responses to 107 attitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 28 publications
(52 reference statements)
6
51
1
Order By: Relevance
“…Fast-food consumption was most prevalent in young adults, high income level groups and middle education level groups. These demographic findings have also been observed overseas (10,11,(18)(19)(20)30) and reflect the target market of the fast-food industry, especially in Asia (31) .…”
Section: Discussionsupporting
confidence: 61%
“…Fast-food consumption was most prevalent in young adults, high income level groups and middle education level groups. These demographic findings have also been observed overseas (10,11,(18)(19)(20)30) and reflect the target market of the fast-food industry, especially in Asia (31) .…”
Section: Discussionsupporting
confidence: 61%
“…The association between socio-economic position (SEP) and takeaway food has been examined in a number of Australian (1)(2)(3)(4)(5)(6) and international studies (7)(8)(9) . To date, the findings of such studies are mixed, with some studies showing that socio-economically advantaged groups are more likely to purchase or consume takeaway food (2,5,7) and others reporting the opposite (1,4,8,9) or no association (3,6) .…”
mentioning
confidence: 99%
“…Given that the time costs for meals must consider all aspects, including preparation, eating and cleaning time (35) , this association may be related to a greater amount of time afforded to these women through not having paid work commitments. Alternatively, those who do work may be under more time pressure, which may increase the demand for convenience products such as fast food (24,(36)(37)(38) . Further, blue-collar employees may work non-standard working hours (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies have revealed that a higher consumption of, or expenditure on, FPOH is associated with less-healthy nutritional profiles in Westernised countries such as Australia (14) , the USA (8,9,18) and countries within Europe (19,20) . Although increased socio-economic disadvantage has been linked to lower dietary quality (21)(22)(23) , and specifically to increased fast-food consumption (22,(24)(25)(26) , less is known about predictors of more general out-of-home purchasing (14,20) or of consumption of meals prepared at home. In addition, it is rare for studies examining predictors of eating behaviour to consider multiple places of consumption, or multiple indicators of socio-economic position.…”
mentioning
confidence: 99%